Questionnaire for studying the process and result of the trading for the needs of forensic commercial examination and evalution activity (Economics and region, 2023)
Questionnaire for the study of the process and the result of the auction for the needs of forensic commodity examination and evaluation activities. The expediency of using marketing research when establishing the numerical values of adjustment coefficients for bargaining is substantiated. The questionnaire process was developed based on the classic basic principles of marketing research and adapted to the given needs. A questionnaire was created for the survey of shoe sellers in e-commerce with the aim of establishing the numerical values of the adjustment coefficient for the auction for the needs of forensic commodity examination and evaluation activities, which allows obtaining: data about the seller of the product, data about the product, questions for a telephone survey (relevance of the offer, willingness to provide discount, the size of the discount) and survey results. The developed questionnaire was used to survey shoe sellers in e-commerce. The implementation of the numerical values of the coefficients of adjustment for bargaining, obtained with the help of the developed questionnaire, into the practice of forensic commodity examination, will contribute to the objectivity and completeness of the expert study and the achievement of correspondence between the result of determining the market value of goods and the real state of their market.
Keywords: forensic commodity examination; evaluation activity; bargaining; marketing research; questionnaire